RENTAL FEE CALCULATION PROGRAM IN FIGURING USING PHP AND MYSQL - Novita Priharti; Erick Orlando, Skom, MMSI (Jurnal Sistem Informasi, 2006)
Along the development of internet technology in Indonesia, the world's internet business was started in interest. Internet cafe is one of the booming business done by business people in Indonesia. In this business the necessary accuracy and speed in counting the cost, and also leases data storage. Based on the above ideas, scientific writing is about the creation of billing system for internet cafe that is used to calculate the cost to rent and store transaction data. This web-based application works in client-server consists of two main form that uses a web programming language PHP4 and MySQL to database.